1979
DOI: 10.1111/j.1432-1033.1979.tb04251.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of a Phosphorylase (Phosphoprotein) Phosphatase Associated with an Alkaline Phosphatase of Mr 35000 from Bovine Adrenal Cortex

Abstract: A metal-ion-independent, nonspecific phosphoprotein phosphatase (MI = 35 000) which represents the major phosphorylase phosphatase activity in bovine adrenal cortex has been purified to apparent homogeneity. An alkaline phosphatase activity (p-nitrophenyl phosphate as a substrate) of the same molecular weight, which requires both a metal ion (Mg2+ > Mn2+ > Co2+) and a sulfhydryl compound for activity, has been found to co-purify with the phosphoprotein phosphatase throughout the purification procedures. Charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Interaction with elements of the peptide in addition to phospho-serine or -threonine is clearly critical, since K m values for protein substrates are much lower than that of artificial substrates like paranitrophenyl phosphate (29). Unlike the protein kinases, where short peptides encompassing the phosphorylation site contain the structural elements necessary for efficient enzyme binding, similar studies with the PPases have been much less informative (30).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction with elements of the peptide in addition to phospho-serine or -threonine is clearly critical, since K m values for protein substrates are much lower than that of artificial substrates like paranitrophenyl phosphate (29). Unlike the protein kinases, where short peptides encompassing the phosphorylation site contain the structural elements necessary for efficient enzyme binding, similar studies with the PPases have been much less informative (30).…”
Section: Discussionmentioning
confidence: 99%
“…PP2A, a dual specificity phosphatase capable of dephosphorylating tyrosyl residues as well as serine/threonine residues (65,66), plays a role in a multitude of cellular functions (reviewed in Ref. 34).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that a major p-nitrophenyl phosphatase activity co-purified with this phosphorylase phosphatase activity [16]. It has been known for some time that p-nitrophenyl phosphatase [17,18] and low phosphotyrosyl phosphatase activities [19,20] are associated with this type of enzyme, and highly variable but so far unexplained p-nitrophenyl phosphate/phosphorylase phosphatase activity ratios have been reported [21,22]. The p-nitrophenyl phosphatase activity is specifically inactivated during purification, but can be restored by incubation with ATP, its analogues or PPi [16].…”
Section: Introductionmentioning
confidence: 96%